PEMILIHAN MINYAK PELUMAS/OLI KENDARAAN BERMOTOR - Arnoldi, Dwi (AUSTENIT, 2009)
Lubricant oil is one of the important factor that must be paid attention in a machine maintenance. Majority lubricant oil choosed based on SAE parameter according to the machine specification such us 5W50, 15W50, 15W40 etc. But beside that there are something else very important to know the quality of the lubricant oil that we use itâ€™s â€œSertification Standardâ€ such us API (American Petroleum Institute), ACEA (Association Des Constructeurs Europeen dâ€™Automobiles), ILSAC (Erupe), JASO (Japan Automotive Standard Organization), and the other specification standards that special from producer company to legitimate lubricant, mean that the lubricant oil tested and agree on decided by the producer for used in there production vehicle.